PERAN MEDIA SOSIAL SEBAGAI ALAT PENCAPAIAN SUARA KEADILAN DALAM PENEGAKAN HUKUM DI INDONESIA : NO VIRAL NO JUSTICE - Lu Sudirman; Antony (Paulus Law Journal, 2023)
The phenomenon of “no viral no justice” that emerged on social media reflects the pessimistic attitude of the Indonesian society towards law enforcement. People have found a new legal culture in law enforcement, particularly by using social media as a tool for social control (civil engagement). However, the participation of the public on social media has had negative impacts due to the lack of alignment between legal awareness and emotional reactions to the law. The excessive reliance on emotional reactions has created an unhealthy legal culture and can influence the law enforcement system. The urgency of this research is driven by the increasingly alarming condition of law enforcement in Indonesia, which has led to public participation (people power) that tends to influence and hinder the law enforcement process. The pressures imposed on law enforcement authorities create legal uncertainty and undermine justice itself. Therefore, the discussion on the role of social media as a tool for the public's pursuit of justice in law enforcement in Indonesia is important and relevant for further study. This research aims to examine the influence and relationship of democratic public participation through social media in realizing the three fundamental legal values: justice, certainty, and utility. The research methodology used in this study is socio-legal research. The findings demonstrate that public participation through social media in monitoring the law enforcement process is essential in achieving justice, certainty, and utility. To minimize the emergence of an unhealthy new legal culture (monitoring) in society, it is necessary to enhance legal awareness and conduct targeted monitoring based on thoughtful thinking, reasoning, and argumentation.